1993
DOI: 10.1038/nbt0393-387
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Culture Conditions on IgM Antibody Structure, Pharmacokinetics and Activity

Abstract: Culture conditions affect the binding activity, charge heterogeneity, conformational stability, glycosylation, and pharmacokinetics of human monoclonal IgM HMAB-10058. The 10058 human/human/murine trioma was grown in serum-free airlift suspension culture, hollow fiber perfusion culture, or in nude mouse ascites. The ascites-produced antibody showed reduced conformational stability, greater charge and glycoform heterogeneity, and a lower average degree of sialylation than the in vitro culture-produced material.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(26 citation statements)
references
References 25 publications
3
23
0
Order By: Relevance
“…Therefore, except for the sialylation degree, EPO glycosylation was not significantly modified by the serum removal from the culture medium, which suggests that the intracellular process of EPO glycosylation involving numerous glycosyltransferases and glycan precursors seems to be not compromised. This phenomenon was already reported in the literature as serum was shown to affect the sugar content of the glycans of glycoproteins, particularly by decreasing the sialylation degree which is known to play a critical role in their biological activity (Patel et al 1992;Megaw and Johnson 1979;Maiorella et al 1993;Lamotte 1997;Gawlitzek et al 1995). However, these results seem to be closely dependent on the molecule investigated and of the culture conditions used (Gawlitzek et al 1995) as other papers reported a minor effect of the serum on the glycosylation pattern of recombinant proteins (Lifely et al 1995;Moellering et al 1990;Kopp et al 1996).…”
Section: Discussionsupporting
confidence: 54%
“…Therefore, except for the sialylation degree, EPO glycosylation was not significantly modified by the serum removal from the culture medium, which suggests that the intracellular process of EPO glycosylation involving numerous glycosyltransferases and glycan precursors seems to be not compromised. This phenomenon was already reported in the literature as serum was shown to affect the sugar content of the glycans of glycoproteins, particularly by decreasing the sialylation degree which is known to play a critical role in their biological activity (Patel et al 1992;Megaw and Johnson 1979;Maiorella et al 1993;Lamotte 1997;Gawlitzek et al 1995). However, these results seem to be closely dependent on the molecule investigated and of the culture conditions used (Gawlitzek et al 1995) as other papers reported a minor effect of the serum on the glycosylation pattern of recombinant proteins (Lifely et al 1995;Moellering et al 1990;Kopp et al 1996).…”
Section: Discussionsupporting
confidence: 54%
“…Furthermore, increased levels of cellular-derived substances such as DNA are prone to complicate cell/medium separations (Maiorella et al, 1991). The release of proteases and other intracellular enzymes can result in oxidation, deamination and oligosaccharide hydrolysis of the proteins of interest (Karl et al, 1990;Mohan et al, 1993;Van Erp et al, 1991) with deleterious consequences such as enhanced clearance rates of injected products in therapeutic applications (Goochee and Monica, 1990;Maiorella et al, 1993;Prior et al, 1989).…”
Section: Introductionmentioning
confidence: 95%
“…Although there is one consensus sequence on each IgG Fc H chain for an asparagine-linked sugar chain, the variable region of L and H chain may also be glycosylated (Abel et al, 1968;Spielberg et al, 1970). The carbohydrate on the Fc portion of immunoglobulin has been shown to be involved in different events like complement activation through the binding to Clq (Duncan and Winter, 1988), Fc receptor binding, antibody-dependent cellular cytotoxicity, and feedback immunosuppression, in many cases without affecting antigen binding (Maiorella et al, 1993;Robinson et al, 1994).…”
Section: Discussionmentioning
confidence: 97%
“…Only a limited number of papers have been published on the effect of culture conditions on antibody structural and functional homogeneity (Maiorella et al, 1993;Patel et al, 1992). Investigations on murine IgM production indicated that antibody structure, activity, and pharmacokinetics were dependent on culture conditions, resulting in wide differences in binding activity and clearance rate according to the production method used (Maiorella et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation